Passage through Hell : Modernist Descents, Medieval Underworlds - Pike, David L. (David Lawrence), 1963- (Book collections on Project MUSE., 1997)
Pike's readings of Louis-Ferdinand Celine and Walter Benjamin reveal the tensions at work in the modern appropriation of structures derived from ancient and medieval descents. His book shows how these structures were redefined in modernism and persist in contemporary critical practice. In order to recover the historical corpus of modernism, he asserts, it is necessary to acknowledge the attraction that medieval forms and motifs held for modernist literature and theory. By pairing the writings of the postwar German dramatist and novelist Peter Weiss with Dante's Commedia, and Christine de Pizan with Virginia Woolf, Pike argues for a new level of complexity in the relation between medieval and modern poetics.